Palestra de aconselhamento contraceptivo: para quê? - Berardi, Marília Cristina (2017)
Objective: To evaluate the impact of multidisciplinary contraceptive counseling lectures related to the efficacy and individual choices of contraceptive methods. Methods: Sociodemographic variables, preferred methods, opinion about the efficacy of contraceptive methods, and the level of interference of the lecture on the contraceptive choice of 101 participants were analyzed. Results: Female participants primarily chose tubal ligation as a contraceptive option (p=0.55), whereas male participants opted for vasectomy. After the lecture, a lower percentage of men declared that they did not know which method was more efficacious (24.3% versus 0.0%; p=0.006). Also, a lower percentage of women (12.7% versus 1.8%; p=0.020) and men (25.5% versus 7.7%; p=0.003) reported that they did not know which method was less efficacious. Number of children increased the likelihood of choosing an irreversible method in a 30.87-fold (95% CI, 5.503 to 173.168, p<0.001). Conclusion: The lecture impacted on participants' opinions about the efficacy of contraceptive methods, making them have more informed choices. However, it did not influence their choice of contraception. Number of children was the most determining factor in choosing irreversible methods. Practice implications: Family planning programs should rethink lecture-based, in-service educational approaches if their aim is to foster the conscious practice of sexuality.